SCIENTIFIC BASIS OF CERTIFICATION AND STANDARDIZATION OF ENERGY-SAVING TECHNOLOGIES - Kasimov , Sandjar (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
The article analyzes the scientific basis of certification and standardization of energy-saving technologies, their regulatory and technical aspects, and their role in improving energy efficiency. Existing GOST standards, energy consumption indicators, and intelligent management systems were studied. The results indicate that implementing and certifying energy-saving technologies can enhance economic, ecological, and technical efficiency.